PIROLISIS LIMBAH PANGKAL BAMBU MENJADI KARBON AKTIF DAN ASAP CAIR MENGGUNAKAN ZAT AKTIVATOR ASAM PHOSFAT - Purwanti, Ani (IST AKPRIND YOGYAKARTA, 2017)
An inefficient utilization of bamboo resulted in bamboo base as waste withouteconomical value. Converted this bamboo waste becomes active carbon throughpyrolysis will add more value of the product. This study aims to determine the parameterswhich influence the pyrolysis of bamboo waste, to determine the activity of the obtainedactive carbon and liquid smoke yield. The preparation of raw material was conducted bycutting the bamboo into the size of an average length of 4.33 cm, 1.43 cm wide, and 0.48cm high, also analyzed the water content. Pyrolisis was done for 60 minutes in the rangeof temperature between 250°C to 450°C. Activation methods varied by soaking in dilutedphosphoric acid solution (6-14%) prior to pyrolysis with variations in dipping time andtemperature pyrolysis. Yield and reactifity of obtained active carbon and also yield ofliquid smoke were analyzed. With 100 gram of raw material, 60 minutes of reaction time,and activation for 24 hr resulted in an optimum yield of active carbon 27,43% withreactivity 433,99 mg/g under 12% of phosphoric acid solution at 450°C, and the yield ofliquid smoke was 54 mL. GC-MS results showed that acetic acid (30.33%) as a majorcomponent, while 2-propanone (14,34%), methanol (10,37%), 2-butanone (3,75%),acetaldehyde (3,59%), furfural (2,95%), corylon (2,21%), cyclopropyl carbinol (2,11%),phenol (2,1%), glycol (1,85%), dan carbonic acid (1,28%) as a minor component.